Bank Stress Testing of Physical Risks under Climate Change Macro Scenarios : Typhoon Risks to the Philippines - Hallegatte, Stephane (IMF Working Papers; Working Paper, 2022)
Bank stress tests of climate change risks are relatively new, but are rapidly proliferating. The IMF and World Bank staff collaborated to develop an experimental macro scenario stress testing approach to examine physical risks for banks by building a dynamic stochastic general equilibrium model linked to global climate and a catastrophe risk model specifically for the Philippines. Our model shows that the impact of extremely rare typhoons on GDP could already be systemic and worsen substantially with climate change. However, bank capital declines only modestly unless the event is compounded with other disasters, partly thanks to the strength of Philippines' banks and economy before the COVID crisis. However, more work is needed before drawing strong conclusions about the relevance of climate risk, as the model focused only on typhoons' physical capital destructions and their macroeconomic-level transmissions to banks.